2022
DOI: 10.1002/deo2.107
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic portal venous gas and bacteremia after colonic endoscopic submucosal dissection: A case report

Abstract: Hepatic portal venous gas (HPVG) is considered to be a sign of poor prognosis in abdominal diseases and a potentially fatal condition. However, HPVG after colonic endoscopic submucosal dissection (ESD), is an even rarer complication that there is just one report of it at the moment. In this report, we present a case of HPVG and bacteremia that happened a day after colonic ESD in the descending colon. A 79‐year‐old female was referred to perform endoscopic treatment for a 40‐mm elevated tumor in the descending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…It is not an independent disease but is usually accompanied by digestive tract diseases such as intestinal obstructive disease, mesenteric vascular disease, 4 gastric ulcers 5,6 gastric cancer, 7 peptic ulcers, 4 endoscopic and radiation surgery. 813 Previous reports have indicated that HPVG is often associated with severe intestinal diseases and has a mortality rate of up to 75%. 4 It is also often considered an indication for emergency abdominal surgery and has been termed the “sign of death.” As a result of the enormous progress and development in the field of medicine, Kinoshita et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is not an independent disease but is usually accompanied by digestive tract diseases such as intestinal obstructive disease, mesenteric vascular disease, 4 gastric ulcers 5,6 gastric cancer, 7 peptic ulcers, 4 endoscopic and radiation surgery. 813 Previous reports have indicated that HPVG is often associated with severe intestinal diseases and has a mortality rate of up to 75%. 4 It is also often considered an indication for emergency abdominal surgery and has been termed the “sign of death.” As a result of the enormous progress and development in the field of medicine, Kinoshita et al.…”
Section: Discussionmentioning
confidence: 99%